The issues behind agitations, conflict and war: a case of Nigeria - Terwase, Isaac Terungwa; Yerima, Hindatu Maigari; Abdul Talib, Asmat Nizam; Ibrahim, Muhammad Bello (EconJournals, 2016)
Nigeria serves as a destination for marketing of goods and services, as such, her strategic position in Africa calls for concern on political, social and economic issues that may bedeviled the growth and development of the country.Nigeria as a country went through numerous challenges in the past such as the military takeover of political governance, from 1966-1979, and 1983-1999 when the military officers were in power. They handed over power in 1999 during the return to civilian rule. The paper seeks to investigate the issues behind the agitations in Nigeria that led to conflicts during the 2011 general elections and the agitations after 2015 general elections.The paper made use of qualitative approach through the conduct of interviews, use of internet sources such as academic journals, online newspapers and review of previous literature as sources of data collection.The findings reveals that, conflicts arising from the 2011 general elections led to the continuous attacks on the Nigerian State by the Boko Haram insurgents, and the defeat of the incumbent president in 2015 general elections led to the new agitation for the secession of Biafra from the Nigerian state.